STUDI KUALITAS AIR DI LINGKUNGAN PERAIRAN TAMBAK ADOPSI BETTER MANAGEMENT PRACTICES (BMP) PADA SIKLUS BUDIDAYA I, KELURAHAN KARANG ANYAR PANTAI KOTA TARAKAN PROPINSI KALIMANTAN UTARA - Santosa, Muhammad Budi; Wiharyanto, Dhimas (Jurnal Harpodon Borneo, 2013)
Brackish water pond is one of human making ecosystem. Commonly, It’s use for fisheries production especially shrimp or fishes purporting. In Coastal of North Kalimantan, to running its have been used traditional system. This system is depending to the natural condition. The good water quality is one important thing for supporting life in the waters column and management system. This study for management life organisms in pond we must know about water quality in every day for turn of the risk. Daily and weekly observations on water quality in the pond water obtained under unfavorable conditions. This is indicated by dissolved oxygen conditions which tended lower than normal organisms as well as an increase in the content of ammonia in the course of shrimp farming. To further efforts should be made to the improvement of water quality conducted from land preparation.